Adapting to the challenges of the global pandemic on genetic counselor education: Evaluating students' satisfaction with virtual clinical experiences. Issue 4 (26th July 2021) - Jacobs, Chris; McEwen, Alison
Abstract: Travel restrictions, physical distancing, and limits to clinical placements due to the global pandemic raised enormous challenges for genetic counseling education in 2020. In response, we created authentic virtual clinical experiences in our Master of Genetic Counseling program, mimicking clinical practice: virtual simulation with standardized clients, and virtual clinical placements, including intake calls, triage, consultations, teamwork and time management, and genetic counseling with standardized clients. The virtual clinical experiences involved online pre‐brief, simulation, and debrief. We aimed to evaluate students' satisfaction with this learning method. Between April and November 2020, we distributed an anonymous online survey to all participating students using a modified version of a validated satisfaction with simulation scale. We analyzed the combined responses from first‐ and second‐year virtual clinical experiences using descriptive statistics and content analysis. The total number of possible responses was 120. The mean response rate was 68.36% ( n  = 82.03), with a mean of 16.41 participants responding to each survey from each year group. Of the first‐year participants, 53% ( n  = 10) had not observed a genetic counseling consultation before attending the virtual clinical placement. Overall, 92.5% of responses indicated that students were satisfied with the virtual clinical experiences ( SD  = 0.05). 100% ( n  = 82) of responses indicated that working with standardized clients was beneficial to learning, encouraged reflection on clinical ability and was a valuable learning experience overall. However, 37.78% ( n  = 17) of those who participated in the virtual simulation found that the use of Zoom detracted from their clinical learning. The virtual clinical experiences increased first‐year students' confidence about clinical placement and prepared second‐year students for telehealth. In conclusion, the adaptation to virtual clinical experiences enhanced learning for most students, prepared them for practice, met the requirements of the accreditation body and enabled all of our final year students to graduate on time.